P2RX7 signaling drives the differentiation of Th1 cells through metabolic reprogramming for aerobic glycolysis - Salles, Érika Machado de; Raeder, Paulo Lisboa; Angeli, Claudia Blanes; Santiago, Verônica Feijoli; de Souza, Cristiane Naffah; Ramalho, Theresa; Câmara, Niels Olsen Saraiva; Palmisano, Giuseppe; Álvarez, José Maria; D'Império Lima, Maria Regina (Frontiers in Immunology, 2023)
This study provides evidence of how Th1 cell metabolism is modulated by the purinergic receptor P2X7 (P2RX7), a cation cannel activated by high extracellular concentrations of adenosine triphosphate (ATP). In vivo analysis was performed in the Plasmodium chabaudi model of malaria in view of the great relevance of this infectious disease for human health, as well as the availability of data concerning Th1/Tfh differentiation. We show that P2RX7 induces T-bet expression and aerobic glycolysis in splenic CD4+ T cells that respond to malaria, at a time prior to Th1/Tfh polarization. Cell-intrinsic P2RX7 signaling sustains the glycolytic pathway and causes bioenergetic mitochondrial stress in activated CD4+ T cells. We also show in vitro the phenotypic similarities of Th1-conditioned CD4+ T cells that do not express P2RX7 and those in which the glycolytic pathway is pharmacologically inhibited. In addition, in vitro ATP synthase blockade and the consequent inhibition of oxidative phosphorylation, which drives cellular metabolism for aerobic glycolysis, is sufficient to promote rapid CD4+ T cell proliferation and polarization to the Th1 profile in the absence of P2RX7. These data demonstrate that P2RX7-mediated metabolic reprograming for aerobic glycolysis is a key event for Th1 differentiation and suggest that ATP synthase inhibition is a downstream effect of P2RX7 signaling that potentiates the Th1 response.